Association between Physical Activity Level and Hemoglobin Concentration in Male College Students - Ignatio Rika Haryono; Rika Zaskia; Stefanus Lembar (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Increased physical activity is useful for reducing the risk of most non communicable diseases. However, the effect of high physical activity on hematological profile is not established yet. The aim of this study is to investigate the association of physical activity and hemoglobin concentration in college students. This cross-sectional study involved 67 male students of Faculty of Medicine and Health Science, Atma Jaya Catholic University of Indonesia. The physical activity was evaluated using International Physical Activity Questionnaire (IPAQ). Hemoglobin concentration was measured using a hemoglobinometer. Anova test with LSD post hoc analysis was applied to compare the hemoglobin concentration between groups. Significance was set at p<0.05. There were 17 students (25.4%) with low physical activity, 20 students (29.8%) with moderate physical activity, and 30 students (44.8%) with high physical activity. The hemoglobin concentrations were 15.6g/dL in low physical activity, 14.8 g/dL in moderate physical activity, and 15.2 g/dL in high physical activity. LSD post hoc analysis showed that hemoglobin in low physical activity is significantly higher than in moderate (p=0.027). Students with moderate physical activity had the lowest hemoglobin concentration, and significantly lower than students with low physical activity.